Antinutrients and heavy metals in new Nigerian Musa hybrid peels with emphasis on utilization in livestock production - Adeniji, T.A.; Barimalaa, I.S.; Tenkouano, A.; Sanni, Lateef O.; Hart, A.D. (EDP Sciences, 2008)
Introduction. A comparative study of antinutrients and heavy metals in the peels of five improved varieties of plantain and banana hybrids was investigated. Our aim was to provide information on plantain and banana peels that may circumvent huge losses during fruit processing by converting waste into wealth and health. Materials and methods. Four new plantain hybrids developed at the IITA, Nigeria, named PITA 14, PITA 17, PITA 24 and PITA 26, one cooking banana hybrid (BITA 3) and an African plantain landrace, Agbagba, were investigated. Antinutrient and heavy metal contents of the dried peels from the different cultivars were determined and the data were statistically analyzed. Results and discussion. The plantain hybrid PITA 14 differed significantly from other cultivars in saponin, tannin and oxalate. A significant difference was observed between PITA 17 in phytate compared with other cultivars. Cyanogenic glucosides found in PITA 17, PITA 26 and BITA 3 differed significantly from the values obtained in other cultivars. Both BITA 3 and Agbagba are significantly different from other cultivars in phenolic content, while PITA 24 and Agbagba differed significantly from other cultivars in lead. PITA 24 peels differed significantly from other cultivars in cadmium, but no significant difference was found among the different Musa varieties in mercury. Conclusion. In spite of the antinutritional properties ascribed to the various constituents investigated, the levels found in the peels of new Musa hybrids suggest that new varieties might not constitute a health hazard when ingested. Plantain and banana peels may be converted into livestock feeds, which will eventually provide protein and other nutrients to humans from consumption of meat and other products derived from the animals.